The Effectiveness of Omega-3 Fatty Acid Supplementation in the Management of Periodontal Disease in Patients with Type 2 Diabetes Mellitus - Anggun Rafisa; Dewi Marhaeni Diah Herawati; Sri Tjahajawati; Erli Sarilita (Jurnal EduHealth, 2025)
Type 2 diabetes mellitus is closely associated with periodontitis through chronic inflammation and impaired tissue healing, resulting in a bidirectional relationship that adversely affects both metabolic control and periodontal health. Omega-3 fatty acids possess anti-inflammatory and pro-resolving properties and have been proposed as adjunctive host-modulatory agents in periodontal therapy for patients with diabates. This systematic review aimed to evaluate the effectiveness of omega-3 fatty acid supplementation, alone or in combination with other adjunctive therapies, on periodontal and systemic outcomes in patients with periodontitis and type 2 diabetes mellitus. This review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. A comprehensive literature search was conducted in PubMed and Scopus databases for randomized controlled trials published between 2015 and 2025. Eligible studies investigated omega-3 fatty acid supplementation as an adjunct to nonsurgical periodontal therapy in patients with periodontitis and diabetes mellitus. Data were extracted and synthesized descriptively. Six randomized controlled trials met the inclusion criteria. Adjunctive omega-3 fatty acid supplementation consistently demonstrated greater improvements in periodontal parameters, including probing depth, clinical attachment level, and gingival inflammation, compared with nonsurgical periodontal therapy alone. Omega-3–based interventions were associated with significant reductions in inflammatory and cardiometabolic biomarkers, such as interleukins, pentraxin, chemerin, malondialdehyde, and glycated hemoglobin. Combined interventions, particularly omega-3 with low-dose aspirin or omega-3–enriched cranberry juice, yielded the most pronounced periodontal and metabolic benefits. Omega-3 fatty acids appear to be a promising adjunctive therapy for improving periodontal and systemic outcomes in patients with type 2 diabetes mellitus.